Hydroxytyrosol Attenuates Hepatic Fat Accumulation via Activating Mitochondrial Biogenesis and Autophagy through the AMPK Pathway - Dong, Yan-Zou; Li, Lei; Espe, Marit; Lu, Kang-Le; Rahimnejad, Samad (Journal of agricultural and food chemistry, 2020)
Two experiments were carried out to examine the impacts of hydroxytyrosol (HT) on lipid metabolism and mitochondrial function in Megalobrama amblycephala. Triplicate groups of fish were fed four test diets: (1) low-fat diet (LFD, 5% fat), (2) high-fat diet (HFD, 15% fat), (3) LFD + 100 mg/kg HT (LFD + HT), and (4) HFD + 100 mg/kg HT (HFD + HT) (in vivo). Hepatocytes from the same batch were exposed to three media including L-15 medium (L15), oleic acid (OA) medium [L15 + 400 μM OA], and OA + HT medium [L15 + 400 μM OA + 10 μM HT] to explore the roles of HT in mitochondrial function (in vitro). Fish fed HFD had excessive fat deposition in the liver, and HT inclusion in the HFD decreased hepatic fat deposition. Transmission electron microscopy revealed that the HFD triggers loss of cristae and metrical density and hydropic changes in mitochondria and that HT supplementation attenuates the ultrastructural alterations of mitochondria. The in vitro test showed that HT decreases fat deposition in hepatocytes, suppresses the reactive oxygen species formation, and facilitates the expression of phospho-AMPK protein and the genes involved in mitochondria biogenesis (PGC-1, NRF-1, TFAM) and autophagy (PINK1, Mul1, Atg5). These findings suggest the lipid-lowering effect of HT mediated by activation of mitochondrial biogenesis and autophagy through the AMPK pathway.
Keywords: krmivo pro zvířata; AMP-Activated Protein Kinases; proteinkinasy aktivované AMP; fenethylalkohol; Mitochondria; zvířata; Dietary Fats; Animal Feed; Phenylethyl Alcohol; dietní tuky; autofagie; mitochondrie; Organelle Biogenesis; rybí proteiny; Hepatocytes; hepatocyty; Liver; biogeneze organel; Animals; Autophagy; Fish Proteins; játra; Cyprinidae